The effect of feeding, storage and anticoagulant on feline serum cystatin C. Issue 1 (October 2015) - Ghys, L.F.E.; Paepe, D.; Lefebvre, H.P.; Taffin, E.R.L.; Hesta, M.; Delanghe, J.R.; Smets, P.; Vandendriessche, V.; Daminet, S.
Highlights The effect of feeding, storage and anticoagulant on cystatin C was investigated. Feeding does not influence serum cystatin C and serum creatinine. Freezing caused a significant decrease of both serum and urinary cystatin C after 5 and 12 months both at −20 °C and −72 °C. Plasma cystatin C was significantly lower than serum cystatin C.